Cover Image - Yinnan Mu; Weini Zhang; Pan Qin; Wenxing Li; Zhengwei Cui; Yang Ding; Jingqun Ao; Jiangtao Gao; Xinhua Chen (Reviews in Aquaculture, 2026)
The cover image is based on the article Elucidating the Immunological Basis of Large Yellow Croaker Larimichthys crocea Offers New Strategies for Its Disease Management by Yinnan Mu et al., https://doi.org/10.1111/raq.70164 . image